Pelaksanaan Projek P5 dengan Tema Pemberdayaan Masyarakat melalui Kegiatan Karang Taruna terhadap Perkembangan Membaca Reflektif Siswa SMP - Alisya Nurul Zahra; Ursa Mayori Rohmani; Ichsan Fauzi Rahman (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
The active role of youth organizations such as Karang Taruna in community empowerment is proven to have a positive impact on improving the quality of education, especially in developing the interest and ability of reflective reading of junior high school students. This study aims to evaluate the implementation of Project P5 which integrates the role of Youth Organization as an agent of community empowerment in supporting the development of reflective literacy of junior high school students. The method used is a systematic literature review (SLR) with a literature review approach that is carried out in a structured and systematic manner. Data were collected through literature searches in various trusted academic databases using relevant keywords, then selected based on inclusion and exclusion criteria to ensure the selected sources were of high quality and in accordance with the research focus. Data analysis was conducted qualitatively through narrative synthesis to incorporate study results related to community empowerment, the role of Karang Taruna, and student literacy development. The study findings show that Karang Taruna's involvement in literacy activities can create an atmosphere that supports the growth of a sustainable reading culture and increase students' reflective awareness of the importance of reading as a medium for self-development. Project P5 makes a meaningful contribution in shaping students' character and positive attitude towards education through community empowerment that involves active participation and collaboration of various parties. The results of this study are expected to be a reference for other schools and communities in designing effective community empowerment programs to improve literacy and the overall quality of education.